Pepouza and Tymion: The Discovery and Archaeological Exploration of a Lost Ancient City and an Imperial Estate - Tabbernee, William (Walter de Gruyter, 2008)
This book tells the exciting story of the discovery in July 2000 of Pepouza, the most Holy City in the theology of Montanism, a prophetic sect of early Christianity, and an imperial estate on which Tymion was located. The discovery culminates three years of careful study and preliminary field work preceded by a further thirty years of Montanist research byWilliam Tabbernee who led the discovery. This book also details the archaeological surface survey campaigns conducted from 2001 to 2004 at the sites. These campaigns, directed by original "team"-member Peter Lampe, have already revealed a great deal of specific information concerning the ancient site of Pepouza and the imperial estate around Tymion.